One century of forest rehabilitation in the Philippines: approaches, outcomes and lessons - Chokkalingam, U.; Carandang, A.P.; Pulhin, J.M.; Lasco, R.D.; Peras, R.J.J.; Toma, T. (Center for International Forestry Research, 2006)
Forest cover is decreasing or very low in many tropical landscapes following decades of logging, fire and other human disturbances. At the same time, there are large and growing areas of degraded forest lands that need to be rehabilitated to again provide forest goods and services and meet local livelihood needs. National, international, local and private agencies have invested in innumerable rehabilitation initiatives in the tropics. Lots of money has been spent, but have these efforts actually increased forest cover, helped impoverished upland communities, enhanced biodiversity and environmental services, or contributed to meeting timber needs? Did they address the underlying degradation causes and were the rehabilitated areas maintained in the long term? What are the most promising approaches? Which ones can be replicated at low cost by local institutions and actors? Which ones are self-sustaining at the local level? What enabling factors are required to sustain the efforts?. This report reviewing forest rehabilitation in the Philippines is part of a larger study by the Center for International Forestry Research (CIFOR) and national partners to assess efforts across six countries to try and answer the above questions and derive lessons for planning and guiding future efforts. The countries are Peru, Brazil, Indonesia, Vietnam, China and the Philippines. The study aimed to increase the chances of success for future rehabilitation efforts by identifying the approaches that contributed to longer-term sustainability and positive outcomes for different stakeholders.